Game Real-Time Strategy Conquest War Berbasis Web Menggunakan Finite-State Machine - Jimmy Christian Tanian; Alexander Setiawan; Lily Puspa Dewi (Jurnal Infra, 2021)
With the development of technology today, games are one of the activities that are popular for many people. Starting from children and even adults are also playing videogames. strategy game is the one of them. Of the many real-time strategy games available, there are still many real-time strategy games today that are too complex and difficult for players to understand. In this thesis, a real-time strategy game will be made that is easy to understand and play but does not eliminate the strategy element in the game.In order for this game to be even more interesting, Artificial Intelligence (AI) finite state machine (FSM) was added to this game to regulate the opponent's movements in order to make the game lively. In this game, there are features i.e. save/load to save and load data and sound settings to adjust the sound. The result from 5 respondents that give rating : 76% game control, 68% game graphic, 80% game sound , 80% gameplay dan 80% tutorial clearance.